Numerical investigating the impact of fluid properties and oscillation frequency on micro mixer efficiency - Sajad Ghanbari; Mohammad Sefid; Mohammad Ali Sabbaghi (Heliyon)
In this research, the impact of differing densities and viscosities of two dissolving fluids on their mixing efficiency, as well as the effects of various excitation frequencies on the performance of the mixer, have been examined. For this purpose, a two-dimensional microchannel equipped with an oscillating circular cylinder was used, operating within a Strouhal number range of 0.1–0.55, with an oscillation amplitude of 0.4 cylinder diameters in a direction perpendicular to the flow direction, at a blockage ratio of 13 and Reynolds and Schmidt numbers of 50 and 10, respectively, utilizing a finite volume method based on elements. The results obtained indicate that mixing two identical fluids represents an ideal condition, wherein the highest level of mixing occurs compared to mixing two fluids with differing densities and viscosities. As the difference in viscosity and density between the two fluids increases, the level of mixing decreases, such that an increase in the logarithmic viscosity ratio up to R = 2 results in a 257.66 % reduction in mixing, and an increase in the density ratio up to S = 3 leads to a 170.08 % reduction in mixing efficiency. However, at points where the density and viscosity increase factors are equal (s = eR), the increase in density has a greater impact on reducing the mixing efficiency compared to the increase in viscosity. Specifically, at an increase factor of 3 for both density and viscosity, density has a 50 % greater effect on reducing mixing efficiency than viscosity. Furthermore, it is observed that when two fluids have different densities and viscosities, changes in the Strouhal number have a lesser impact on the mixing index compared to when the two fluids are identical. By creating a difference in viscosity and density between the two mixing fluids, the mixer exhibits unique and distinct performance, such that for each viscosity and density ratio, it is observed different optimal Strouhal numbers independently. This research provides a fundamental understanding of the effects of differing density and viscosity, as well as the impact of excitation frequency on the mixing efficiency of the two fluids.